A retrospective study of choke (oesophageal obstruction) in 64 one‐hump Dromedary camels (Camelus dromedarius) in Saudi Arabia. Issue 1 (25th December 2022) - Zabady, Mohamed K.; Shawaf, Turke
Abstract: Background: Choke (oesophageal obstruction) is an important oesophageal disorder in large domestic animals. Published studies on choke in the dromedary camel ( Camelus dromedarius ) are few in number and deal with small number of cases. Methods: Sixty‐four camels with choke were presented to the Veterinary Teaching Hospital, King Faisal University. History, breed, age, sex, duration of obstruction and clinical signs were recorded. The diagnosis was established using examination with a stomach tube, oesophageal radiography and endoscopy. Choke was managed either by using alligator forceps guided endoscope or by cervical oesophagotomy. Results: Choke was recorded in camels less than 1 year old (84.38%) more than camels more than 1 year of age (15.62%) and complete obstruction more than partial. Most cases had obstruction involving the cervical oesophagus (96.87%). In the majority of obstructive masses, there were pieces of fabric (48.44%) and plastic bags (35.94%). Most obstructive masses were slightly radio‐opaque (62.5%). Surgical and non‐surgical managements were effective (91.3% and 94.44%, respectively) in resolving the choke. Conclusions: Choke was most likely in animals less than 1 year of age with complete obstruction of the cervical oesophagus. Surgical and non‐surgical methods were effective in resolving the choke in the dromedary camels. It was not practical to use forceps extraction in all adult camels due to the limited length of the alligator forceps.